2019
DOI: 10.1007/s00234-019-02161-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiological scales predicting delayed cerebral ischemia in subarachnoid hemorrhage: systematic review and meta-analysis

Abstract: Purpose Delayed cerebral ischemia (DCI) is a severe complication of aneurysmal subarachnoid hemorrhage (aSAH). The extent of subarachnoid blood is a strong predictor of DCI and is frequently estimated with the Fisher scale, modified Fisher scale, or Hijdra sum score. It is unclear which scale has the strongest association with clinical DCI. To evaluate this, we performed a systematic review of the literature. Methods We performed a MEDLINE and EMBASE search from 1980 to 20th of June 2017. Radiological grade an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 71 publications
(28 reference statements)
1
48
0
3
Order By: Relevance
“…e severity of SAH is concerned that it may be the stimulant factor to develop DNID. e literature showed that 40%-70% of ruptured aneurysms patients with highgrade WFNS developed DNID [10,11], whereas FS was demonstrated to be associated with DNID of 55% with multivariable analysis and of 62% with univariable analysis [12]. Moreover, our study considered the types of general anesthetic agents as confounding factors; thus, the simple random sampling with 1 : 2 matching based on WFNS, FS, and general anesthetic agents was conducted for patients distribution as 1 case in the DNID group and 2 controls in the non-DNID group that showed no statistically significant difference between both the groups (p > 0.99) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…e severity of SAH is concerned that it may be the stimulant factor to develop DNID. e literature showed that 40%-70% of ruptured aneurysms patients with highgrade WFNS developed DNID [10,11], whereas FS was demonstrated to be associated with DNID of 55% with multivariable analysis and of 62% with univariable analysis [12]. Moreover, our study considered the types of general anesthetic agents as confounding factors; thus, the simple random sampling with 1 : 2 matching based on WFNS, FS, and general anesthetic agents was conducted for patients distribution as 1 case in the DNID group and 2 controls in the non-DNID group that showed no statistically significant difference between both the groups (p > 0.99) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies demonstrated low sensitivity and specificity of this scale for predicting DCI [6][7][8][9][10]. Recently, a systematic review assessing the association of radiological scales for grading aSAH with DCI showed that patients with Fisher grade 4 have a significantly lower risk of DCI compared to those with Fisher grade 3 [13]. With current clinical management including nimodipine, hypertensive therapy, and endovascular treatment, the Fisher grade predicts symptomatic vasospasm in only half of cases [14].…”
mentioning
confidence: 99%
“…This includes prescribing nimodipine (a calcium channel blocker that has been proven to improve outcome, probably through influencing cortical spreading ischaemia and microthromboembolism) [26][27][28] , maintaining normal intravascular volume status, temperature, electrolytes, glucose and adequate cerebral perfusion pressure by maintaining adequate blood pressure. 13,29 Prophylactic use of hypervolaemia 30,31 or balloon angioplasty 32 in order to improve CBF has been found non beneficial in improving outcome after aSAH.…”
Section: Definition Of DCImentioning
confidence: 99%
“…[33][34][35] However, a meta-analysis showed that only induced hypertension seemed capable of improving CBF, with hypervolaemia being associated with increased risk of complications and haemodilution causing a decrease in oxygen delivery to the brain despite increased CBF. 30 Therefore, several international guidelines nowadays advise treating DCI with induced hypertension combined with euvolemia. 29,36 However, even though induced hypertension is reported to reverse signs of DCI in up to two-thirds of treated patients 37 , sound evidence of its effectiveness is lacking and it is unclear whether induced hypertension actually leads to improved functional outcome.…”
Section: Treating DCImentioning
confidence: 99%
See 1 more Smart Citation